Aromatase is phosphorylated in situ at Serine-118 - Miller, Todd W. (2008)
Phosphorylation of the cytochrome P450 aromatase has been proposed as a switch to rapidly modulate enzymatic activity and estrogen biosynthesis. Herein, we demonstrate that aromatase serine-118 is a potential phosphorylation site in mammalian cells. The amino acid context surrounding S118 is highly conserved among diverse animal species and suggests that an AGC-like kinase may phosphorylate aromatase. Mutation of S118 to Ala blocked phosphorylation. Mutation of S118 to either Ala or Asp destabilized aromatase, indicating an important structural role for S118. The phosphomimetic S118D mutant showed decreased specific enzymatic activity, decreased Vmax, and increased Km, while the S118A phospho-inhibiting mutant showed opposite effects. Our findings suggest that phosphorylation of S118 may decrease aromatase activity, presenting a mechanism whereby kinase signaling may modulate estrogen production and hormone balance.